Q&A - Ask Doubts and Get Answers

Clear All
When a = 0 and b = -1 the value of the given expression 2a2b + 2ab2 + ab = 0
When a = 0 and b = -1 the value of the given expression 2a2 + b2 + 1 = 2
When a = 0 and b = -1 the value of the given expression 2a + 2b = -2
a2 - b2 = 22 - ( -2 )2 = 4 - 4 = 0 If a = 2 and b = -2 the value of a2 - b2 = 0
If a = 2 and b = -2 the value of a2 + ab + b2 = 4
a2 + b2 = ( 2 )2 + ( -2 )2  = 4 + 4 = 8 If a = 2 and b = -2 the value of a2 + b2 = 8
-x + 2 = -( -1 ) + 2 = 1 + 2 = 3 If x = -1 the value of -x + 2 = 3
If p = -2 the value of -2p3 - 3p2 + 4p + 7 = 3  
(i) m - 2 = 2 - 2  = 0 If m = 2 the value of m - 2 = 0
On subtracting the sum of and  from the sum of   and  we get 
On subtracting 3x - y - 11 from the sum of 3x - y + 11 and -y - 11 we get -y + 11
Exams
Articles
Questions